Problematizing Critical Theory: Arriving at a More Critical Critical Theory - Rodriguez, Agustin Martin G (Archīum Ateneo, 2019)
This paper reflects on how critical theory is deeply rooted in Western, European philosophical traditions. It argues that a more radical critical philosophizing could be realized if the rationality of the othered traditions of thinking are brought to bear in critical theorizing.